Australian Mega Transport Business Cases: Missing Costs and Benefits. Issue 4 (2nd October 2019) - Searle, Glen; Legacy, Crystal
ABSTRACT: This paper uses business cases for three contemporary Australian mega transport proposals to examine the extent to which societal costs and benefits are properly evaluated in public investment decisions about such projects. It analyses project-related costs and benefits omitted or inadequately evaluated in the cost-benefit analyses of business cases for Stage 2 (the eastern section) of Melbourne's East West Link tollroad, Sydney's WestConnex tollroad, and Brisbane's Cross River Rail. The omissions identified mean the rationale of business cases to reduce wasteful, politically-driven decisions is being lost. Instead, the omissions help business cases give ex post justification for decisions already made.